Lateral displacement of boundary wall of residential building due to timber piles installation in soft ground - Sailesh Shrestha; Norihiko Miura; Yuki Matsumoto (Lowland Technology International, 2021)
Numerous investigations on piles' behavior in soft ground have been concerned with single piles' bearing capacity and settlement behavior. Relatively, little is known about the implications of installing group piles, such as the lateral displacement caused by driving piles into soft ground. The mechanism of lateral displacement of the ground and the boundary wall (BW) of residential buildings due to the timber pile installation in the soft ground was investigated by a series of three-dimensional (3D) finite element analyses and field measurements. Based on the numerical analyses, the magnitude of the lateral displacement of the ground in the construction site has been quantified at first in this paper after investigating the mechanism in terms of installation patterns, machine movement, auger drilling, type of the pile, the distance of the nearest row of the pile to the BW, and stiffness of the fill material. Then the construction methods to minimize lateral displacement of the boundary wall have been proposed in this study.